Prospective evaluation of serum and peritoneal fluid markers as indicators of postoperative complications in patients with enteric anastomosis - Mladen Kasalović; Božidar Odalović; Lazar Mihajlović; Stefan Jakovljević; Zlatan Elek; Gojko Igrutinović; Milena Anđelković; Mirjana Pajčin (Annals of Saudi Medicine)
BACKGROUND: Postoperative complications of colorectal cancer surgery contribute to increased morbidity and mortality in patients. OBJECTIVES: Investigate the role of biochemical markers in serum and peritoneal fluid in the development of postoperative complications in patients with enteral anastomosis. DESIGN: Prospective. SETTING: University hospitals. PATIENTS AND METHODS: The studied population consisted of patients who underwent surgical treatment with created anastomosis or Hartmann's resection from April 2022 to April 2024, conducted at the Clinical-Hospital Center Kosovska Mitrovica and the University Clinical Center Kragujevac. Spearman's correlation coefficient (rs) was used to test associations between categorical variables. MAIN OUTCOME MEASURES: Lactate, albumin, lactate dehydrogenase, and IgA antibodies were monitored as predictors of anastomotic dehiscence and general postoperative complications. SAMPLE SIZE: 52 RESULTS: The concentration of lactate in the drain fluid on the third postoperative day was statistically significantly higher in patients who did not develop anastomotic dehiscence (P=.006). The concentration of IgA antibodies in the drain fluid on the third and fifth days post-surgery showed a moderate negative correlation with lactate concentration (rs=-.670, P=.012; rs=-.577, P=.039), repectively. There was a significantly higher concentration of albumin in the drain fluid on the third day post-surgery in patients who developed dehiscence (P=.040), and on the seventh day post-surgery in those who did not develop dehiscence (P=.001). The concentration of LDH on the third day in the drain fluid after surgery was statistically significantly higher in patients who did not develop dehiscence (P=.020). There was a statistically significant difference in lactate concentration in the drain fluid on the third (P<.001) and fifth days (P=.041) post-surgery, as well as in albumin concentration on the third day post-surgery (P=.024) with respect to the development of general postoperative complications. CONCLUSION: This study revealed significant differences in the concentrations of lactate, albumin, and LDH in the drain fluid on the third and fifth days post-surgery with respect to the development of complications. These results suggest that monitoring these markers may help in the early identification of patients at risk of complications such as dehiscence. LIMITATIONS: Limited literature on specific aspects of this study, including the absence of a control group, small sample size, and two-center study.